THE EFFECTIVENESS OF COLEUS AMBOINICUS LEAF EXTRACTS AS AN ANALGETIC ACTIVITY ON MICE EXPOSURED TO ACETIC ACID - Pane, Yunita Sari; Sufitni, Sufitni; Lumongga, Fitriani; Alrasyid, Nurfida; Sari, Dini Permata; Wati, Ridha; Basyuni, Mohammad (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This study aims to observe the analgesic activity of Bangun-bangun (Coleus amboinicus) leaves by induction of pain arising from chemical excitement after exposure to acetic acid. Methods: The effectiveness test of water extract and ethanol extract of Bangun-bangun leaves as an analgesic was measured by comparing the mean of quantitative and the writhing between control and treatment group. In addition, observations on the decrease in inflammatory processes occurred by calculating the reduction in the number of leukocyte migration to the inflammatory area. Result: The decrease of excitatory pain in all treatment Groups (I-IV) were significantly different. The comparison of mean values ± SEM decreased excitatory pain Groups I-II (255.00±22.22; 88.33±14.58), p=0.000. Groups I-III (255.00±22.22; 60.00±10.04), p=0.000 and Groups I-IV (255.00±22.22; 50.83±3.09), p=0.000. On histopathology examination, all treatment groups were significantly different (p=0.006). The comparison of mean value ± SEM decrease number of leukocyte Groups I-II (31.73±5.22; 14.70±3.71), p=0.025. Groups I-III (31.73±5.22; 15.67±3.22), p=0.036 and Groups I-IV (31.73±5.22; 11.77±2.77), p=0.008. However, the comparison of decrease of excitatory of pain and number of leukocyte migration between each group did not show significantly different (p>0.05). Conclusions: This study concluded that the Bangun-bangun leaves both in the form of water extract and ethanol extract proved efficacious as a pain reliever in the mice after induction of acetic acid.